The impact of facility-based transitional care programs on function and discharge destination for older adults with cognitive impairment: a systematic review - Alexia Cumal; Tracey J. F. Colella; Martine T. Puts; Poonam Sehgal; Sheryl Robertson; Katherine S. McGilton (BMC Geriatrics, 2022)
Abstract Background Older adults with cognitive impairment are frequently hospitalized and discharged to facility-based transitional care programs (TCPs). However, it is unknown whether TCPs are effective in improving their functional status and promoting discharge home rather than to long-term care. The aims of this systematic review were to examine the effectiveness of facility-based TCPs on functional status, patient and health services outcomes for older adults (≥ 65 years) with cognitive impairment and to determine what proportion post TCP are discharged home compared to long-term care. Methods The Joanna Briggs Institute Critical Appraisal Manual for Evidence Synthesis was used to guide the methodology for this review. The protocol was published in PROSPERO (registration number CRD42021257870). MEDLINE, CINAHL, PsycINFO, the Cochrane Library, and EMBASE databases, and ClinicalTrials.gov and the World Health Organization Trials Registry were searched for English publications. Studies that met the following criteria were included: community-dwelling older adults ≥ 65 years who participated in facility-based TCPs and included functional status and/or discharge destination outcomes. Studies with participants from nursing homes and involved rehabilitation programs or transitional care in the home or in acute care, were excluded. Risk of bias was assessed using the Joanna Briggs Institute Critical Appraisal Checklists. Results are in narrative form. Results Twenty-two studies (18 cohort and four cross sectional studies) involving 4,013,935 participants met inclusion criteria. The quality of the studies was mostly moderate to good. Improvement in activities of daily living (ADLs) was reported in eight of 13 studies. Between 24.4%-68% of participants were discharged home, 20–43.9% were hospitalized, and 4.1–40% transitioned to long-term care. Review limitations included the inability to perform meta-analysis due to heterogeneity of outcome measurement tools, measurement times, and patient populations. Conclusions Facility-based TCPs are associated with improvements in ADLs and generally result in a greater percentage of participants with cognitive impairment going home rather than to long-term care. However, gains in function were not as great as for those without cognitive impairment. Future research should employ consistent outcome measurement tools to facilitate meta-analyses. The level of evidence is level III-2 according to the National Health and Medical Research Council for cohort and cross-sectional studies.